The Rights of Non-Landowner Communities in the National Strategic Project of Bener Dam (Case Study of Wadas Village, Purworejo, Central Java) - Robin Krisna Miswadi (Faculty of Law, Universitas Negeri Semarang, 2025)
Infrastructure development through the National Strategic Project (PSN) in Indonesia often presents challenges related to the protection of the rights of affected communities, especially non-landowner groups. This study examines the rights of affected communities involved in andesite mining activities in Wadas Village, Purworejo, as part of the Bener Dam construction, and evaluates the representation of non-landowner residents in the decision-making process. The research method employed is empirical juridical with normative and sociological approaches, including interviews with residents and analysis of relevant regulations. Findings indicate that although the legal framework regulates land rights, a healthy environment, and compensation, the implementation on the ground is often non-transparent and lacks substantive public participation, particularly for non-landowner residents who are socially and environmentally impacted. Conflicts and structural exclusion arise due to regulatory limitations that recognize only landowners as stakeholders. The study recommends revising land acquisition regulations, strengthening inclusive participation mechanisms, and implementing the Free, Prior, and Informed Consent (FPIC) principle to ensure social justice and sustainable development. This study contributes to the understanding of marginalized communities' rights in the context of national development and provides a policy basis for more equitable rights protection.